2014
DOI: 10.3201/eid2012.141211
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Worker Contact with MERS Patient, Saudi Arabia

Abstract: To investigate potential transmission of Middle East respiratory syndrome coronavirus (MERS-CoV) to health care workers in a hospital, we serologically tested hospital contacts of the index case-patient in Saudi Arabia, 4 months after his death. None of the 48 contacts showed evidence of MERS-CoV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 11 publications
1
51
0
Order By: Relevance
“…19 The seropositivity of HCWs after a contact with MERS-CoV patients is variable. 22 In Korea, 36 (19.9%) of 181 confirmed MERS-CoV cases were HCWs. In a previous study of 1,169 HCWs, 15 were positive by polymerase chain reaction and 5 of 737 HCWs were positive by serology testing.…”
Section: Discussionmentioning
confidence: 99%
“…19 The seropositivity of HCWs after a contact with MERS-CoV patients is variable. 22 In Korea, 36 (19.9%) of 181 confirmed MERS-CoV cases were HCWs. In a previous study of 1,169 HCWs, 15 were positive by polymerase chain reaction and 5 of 737 HCWs were positive by serology testing.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers (HCWs) form a significant risk group for infection [3,4,5]. Most of the cases in health care workers occurred in the early period of the outbreak [6]. The risk of importation of other emerging infectious diseases, particularly with large population movements during the Hajj and Umrah is also significant.…”
Section: Introductionmentioning
confidence: 99%
“…Initial data suggested that the transmission of MERS-CoV among family members was 11-19% based on screening of a small number of contacts of 28-42 family members [14][15][16]. Screening of 462 family members revealed a positivity rate of only 3% by PCR [57]. Further screening of household contacts utilizing both PCR and serology revealed a positivity of 12 out of 280 contacts, showing a positivity rate of only 4% [38].…”
Section: Transmission Of Mers-cov Among Family Contactsmentioning
confidence: 99%